Six key influences on the efficiency of insourcing in state and local plans - Urban, M (Pageant Media, 2018)
State and local pensions can take care of the investment function in-house, or they can outsource part or all of it. Which strategy is the more desirable depends on six key influences: the behavior of cash flows, the significance of economies of scale, asset allocation, staff compensation, a plan’s geographic location, and the scope of fiduciary duty and oversight. These influences have been identified because of their role in the effective management of internal assets and are discussed, taking account of how they vary across institutions. This article does not propose a set of best practices but instead sets out a number of analytical building blocks. It offers a way to think comprehensively about insourcing in institutions that are embedded in different local contexts. In particular, the article gives attention to the influence of local politics and regulation, governance, and geography.